x-9x=-4*6

Simple and best practice solution for x-9x=-4*6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-9x=-4*6 equation:


Simplifying
x + -9x = -4 * 6

Combine like terms: x + -9x = -8x
-8x = -4 * 6

Multiply -4 * 6
-8x = -24

Solving
-8x = -24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-8'.
x = 3

Simplifying
x = 3

See similar equations:

| (8+w)(2w+9)=0 | | 6-2n=1-8n+5 | | 3x+5-6x=10+2x | | -2(z+3)-z=-z-5(z+2) | | x^6+3x^3-4= | | 17x=8x+8 | | -2*-4=o | | 4x-2+2x-5=77 | | 4(5z-1)-5(2+9)=2(z+1) | | 2*-4=o | | -2*-4=ourfgn | | sin(7x)=cos(7x) | | (2d^2-9d)-(-4d^2+20d+17)= | | 2x+(18-x)=11 | | 6(-2)=r+5r | | P(x)=(60x-0.3x^2)-(5x+13) | | 3x+1/3=3x-1/2 | | ln(16x)= | | 5x+14=2+7x | | -1(-1)=z | | 2cos(3x-1)=0 | | 32=2(x+4.5) | | (c^2-9c-5)-(-c^2-8c-10)= | | (x-4)2=(x-2)2 | | x^2-10*x+13=0 | | x^2-10*x+13= | | 7v-28=9+3v-1 | | (11b^2-7)+(15b^2-b)= | | (6y-8)+(5y-3)+(6y+4)=180 | | 50=.5*20V^2 | | -26.3+0.1p=0.9+5.3 | | 2y-5x=-8 |

Equations solver categories